2010
DOI: 10.1007/s12010-010-8950-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biodegradation of a Sulfonated Phenylazonaphthol Dye by a Bacterial Community Immobilized in a Multistage Packed-Bed BAC Reactor

Abstract: A microbial community able to aerobically degrade the azo dye Acid Orange 7 was selected from riparian or lacustrine sediments collected at sites receiving textile wastewaters. Three bacterial strains, pertaining to the genera Pseudomonas, Arthrobacter, and Rhizobium, constitute the selected community. The biodegradation of AO7 was carried out in batch-suspended cell culture and in a continuously operated multistage packed-bed BAC reactor. The rapid decolorization observed in batch culture, joined to a delay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 52 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…are common soil bacteria that form plant nodules and have the enzyme nitrogenase for fixing nitrogen. Biodegradation of sulfonated phenylazonaphthol dye (Ruiz-Arias et al 2010) and phenol (Wei et al 2008) was found to be associated with Rhizobium sp. While Microbacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…are common soil bacteria that form plant nodules and have the enzyme nitrogenase for fixing nitrogen. Biodegradation of sulfonated phenylazonaphthol dye (Ruiz-Arias et al 2010) and phenol (Wei et al 2008) was found to be associated with Rhizobium sp. While Microbacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Ruiz-Arias et al worked on the discoloration of acid orange with the help of a bacterial consortium Pseudomonas, Arthrobacter and Rhizobium. The results showed complete discoloration at a concentration of 200 mg/l, pH 7 [48].…”
Section: Bacterial Methodsmentioning
confidence: 94%
“…Such an acid is susceptible to decomposition by the same consortium under aerobic conditions. About 97% decomposition within 24 hours of direct blue dye 15 with a concentration of 250 mg/l (98 COD) is reported by Jain et al and Ruiz-Arias et al worked on the discoloration of acid orange with the help of a bacterial consortium [47,48]. Ruiz-Arias et al worked on the discoloration of acid orange with the help of a bacterial consortium Pseudomonas, Arthrobacter and Rhizobium.…”
Section: Bacterial Methodsmentioning
confidence: 98%
“…In detail, bacterial genera Rhizobium, Rhodobacter, Altererythrobacter, and Dyella were enriched in the six treated samples. Relevant literatures showed that species belonging to Rhizobium and Rhodobacter could degrade azo dyes and other aromatic compounds (Bin et al, 2004;Huang et al, 2016;Ruiz-Arias et al, 2010;Song, Zhou, Wang, Yan, & Du, 2003). Some of them were even halotolerant species (Diagne et al, 2017;Tangprasittipap, Prasertsan, Choorit, & Sasaki, 2007).…”
Section: Discussionmentioning
confidence: 99%